2012
DOI: 10.1121/1.4757735
|View full text |Cite
|
Sign up to set email alerts
|

Consonant recognition as a function of the number of stimulation channels in the Hybrid short-electrode cochlear implant

Abstract: Consonant recognition was measured as a function of the number of stimulation channels for Hybrid short-electrode cochlear implant (CI) users, long-electrode CI users, and normal-hearing (NH) listeners in quiet and background noise. Short-electrode CI subjects were tested with 1-6 channels allocated to a frequency range of 1063-7938 Hz. Long-electrode CI subjects were tested with 1-6, 8, or 22 channels allocated to 188-7938 Hz, or 1-6 or 15 channels from the basal 15 electrodes allocated to 1063-7938 Hz. NH li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…As a consequence of cochlear sensory epithelial cell loss, the degeneration of cochlear nerve fibers and SGNs is, in essence, atrophy from disuse, which results from the loss of the target organ and neurotrophic factors [1]. With the aid of stem cell transplantation [2], gene rescue [3], neurotrophic factor inner ear administration [1] and other means, hair cell regeneration has already been achieved in many scientific experiments. Hair cell regeneration in vivo is meaningless if the regenerated hair cells cannot be innervated by SGNs in the cochlea.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of cochlear sensory epithelial cell loss, the degeneration of cochlear nerve fibers and SGNs is, in essence, atrophy from disuse, which results from the loss of the target organ and neurotrophic factors [1]. With the aid of stem cell transplantation [2], gene rescue [3], neurotrophic factor inner ear administration [1] and other means, hair cell regeneration has already been achieved in many scientific experiments. Hair cell regeneration in vivo is meaningless if the regenerated hair cells cannot be innervated by SGNs in the cochlea.…”
Section: Introductionmentioning
confidence: 99%
“…The number of surviving SGNs determines the effect of cochlear implantation. Therefore, to achieve better hearing rehabilitation via cochlear implantation, a required number of surviving SGNs is necessary [2,3]. To rehabilitate hearing diminished by sensorineural hearing loss, preventing or alleviating the degeneration of cochlear nerve fibers and SGNs following sensory epithelial cell loss is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…When residual hearing is preserved, patients may utilize both electric and acoustic hearing in the implanted ear. The benefits of combined electric and acoustic hearing in the same ear include better hearing in background noise and in quiet, and better spatial localization (Reiss, Turner, Karsten, Erenberg, Taylor & Gantz 2012a; Gantz et al 2009; Turner et al 2008; Gantz & Turner 2004; Gifford et al 2014; Kiefer et al 2005). These benefits occur when the preserved hearing is in the functional acoustic range (less than 90 dB pure tone average for 125Hz to 1.5KHz) (Roland et al submitted 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Delayed post-implantation hearing loss has been reported in 15 to 56% of patients with initially preserved hearing (Gifford et al 2013; Reiss, Turner, Karsten, Erenberg, Taylor & Gantz 2012b; Van Abel et al 2015; Lenarz et al 2013; Adunka et al 2013). In the Hybrid 10 clinical trial, for example, although only 2 out of 87 patients were found to have total hearing loss at the initial one month follow up, an additional 6 patients progressed to total hearing loss between 3 and 24 months after implantation(Gantz et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Reconstitution of the OC would require an adjustable strategy that takes the local variation of the OC deterioration into account. Such a strategy could start with mapping precisely the residual hearing capacity currently used with short cochlear implants . Even more desirable would be increased imaging resolution to identify not only residual cell types and their distribution, but have precise measurements of the apparently very variable cochlear duct and hearing loss‐related cellular loss .…”
Section: Can Developmental Insights Be Used For In Situ Regeneration?mentioning
confidence: 99%